Does financial inclusion affect monetary policy in SAARC countries? - Sanjaya Kumar Lenka; Arun Kumar Bairwa (Cogent Economics & Finance, 2016)
Alike the role of heart for human body, finance is the focal point of an economy, whereas savings and investment are its tubes and vessels. Hence, a solid financial system is a fundamental character of an enduring economy. The frozen financial system endures longer if its foundation is concrete and subsists in the people of grass-root level. They are those, who live in villages and small towns, earn meager income, work in primary sector, spend more on food, and have lesser social securities. In this setting, the process of bringing these people into the main stream of financial activities is called financial inclusion. This study describes the impact of financial inclusion on monetary policy of South Asian Association for Regional Cooperation (SAARC) countries from 2004-2013. The study uses principal component analysis (PCA) to construct a Financial Inclusion Index that serves as a proxy variable for the accessibility of financial inclusion in the SAARC countries. Adding to it, three different models like FEM, REM, and Panel-corrected standard errors are used for the analysis. In this study, an empirical result of generalized least square(GLS) estimation shows that financial inclusion, exchange rate, and interest rate are negatively associated with inflation in SAARC countries.
Keywords: E44; E51; E52; F36; 330; financial inclusion; monetary policy; principal component analysis (PCA); panel-corrected standard errors (PCSEs)